2010
DOI: 10.1186/1471-2105-11-559
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and deconvolution of asymmetric LC-MS peaks using the bi-Gaussian mixture model and statistical model selection

Abstract: BackgroundLiquid chromatography-mass spectrometry (LC-MS) is one of the major techniques for the quantification of metabolites in complex biological samples. Peak modeling is one of the key components in LC-MS data pre-processing.ResultsTo quantify asymmetric peaks with high noise level, we developed an estimation procedure using the bi-Gaussian function. In addition, to accurately quantify partially overlapping peaks, we developed a deconvolution method using the bi-Gaussian mixture model combined with statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…In the current study, we merged metabolites from HMDB 29 and features found from the example dataset of the apLCMS package 9, 20 . The data was generated using anion exchange column with formic acid gradient combined electrospray ionization (ESI) 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we merged metabolites from HMDB 29 and features found from the example dataset of the apLCMS package 9, 20 . The data was generated using anion exchange column with formic acid gradient combined electrospray ionization (ESI) 30 .…”
Section: Methodsmentioning
confidence: 99%
“…The apLCMS package conducts retention time deconvolution using the bi-Gaussian mixture model to separate features sharing m/z 20 . Thus the feature list from the new data may contain features with almost identical m/z values and different retention time values.…”
Section: Methodsmentioning
confidence: 99%
“…Other algorithms try to improve the peak detection accuracy through better modeling of chromatographic peaks. For example, a bi-Gaussian mixture model have been used for peak detection 44 . However, the fitting of the model to a particular dataset often needs to be checked as chromatographic peak characteristics vary among experiments and instruments.…”
Section: Pre-processing Of Lc-ms Datamentioning
confidence: 99%
“…3), then curve-fit with a bi-Gaussian model (Yu and Peng, 2010). When compared to non-averaged data in Table 1, this averaged data showed smaller peak changes and longer decay times in all amplitude-related EEG measures with similar time to peak changes (Table 2).…”
Section: Resultsmentioning
confidence: 99%